Translation, cultural adaptation, and descriptive psychometric pilot evaluation of the Swedish Cancer Support Source-caregiver - Maria Samuelsson; Jenny Jakobsson; Benjamin Maus; Carl Magnus Olsson; Marie Louise Möllerberg (BMC Health Services Research, 2026)
Abstract Objective This study aimed to translate the CancerSupportSource-Caregiver (CSS-C), culturally adapt it, and conduct a descriptive pilot evaluation of the psychometric properties of the Swedish version in a sample of Swedish family members of persons diagnosed with cancer. Method Translation and cultural adaptation involved forward-backward translation by professional translators in collaboration with the research team and assessments of comprehensibility and face and content validity by two expert panels comprising family members of persons diagnosed with cancer and healthcare professionals, respectively. The psychometric properties, validity, and reliability of the Swedish version were pilot evaluated using classical test theory among a sample of 30 adult Swedish family members of persons diagnosed with cancer. Results Based on requests from the expert panels, and supported by empiricism, the CancerSupportSource-Caregiver was adapted to the Swedish context, and five items were added. Thus, the Swedish version comprises 24 items. The face and content validity of the Swedish CancerSupportSource-Caregiver were satisfactory, and the convergent validity was promising. Moreover, the psychometric pilot evaluations indicated high data quality, overall satisfactory targeting, and internal consistency. However, two items were right-skewed, and there were indices of redundancy. Conclusion The Swedish CancerSupportSource-Caregiver appears to have the potential to identify unmet needs and symptoms of anxiety and depression among Swedish family members of persons diagnosed with cancer. Since the focus of this study was on translating and adapting the tool, further studies in larger samples are warranted to determine the psychometric properties, factor structure, validity, and reliability.